Morphometric analysis of gametes and embryos is crucial for optimizing Intracytoplasmic Sperm Injection outcomes - Mohammad Taghi Vajed-Ebrahimi; Armin Attaranzadeh; Mahmood Reza Golzarian; Abbas Parham (Cellular, Molecular and Biomedical Reports)
Morphometric analysis of gametes and embryos is crucial for optimizing Intracytoplasmic Sperm Injection (ICSI) outcomes. This study aimed to evaluate the importance of morphometric parameters at oocyte, zygote, and embryo stages, focusing on their potential as indicators of developmental competence and quality. A comprehensive analysis was conducted on key morphometric ratios, including the total embryo area to blastomere area (TEa/Ba), total oocyte area to polar body area (TOa/PBa), and oocyte area to polar body area (Oa/PBa), using ART-derived samples categorized into quality classes (Hight (A), medium (B), and low (C)). The materials and methods included precise imaging and statistical evaluation of the structural differences influenced by factors such as maternal age, hormonal levels (FSH, LH), and developmental progression. The results revealed significant differences in the morphometric parameters across quality classes (p-value < 0.05). While maternal age did not significantly affect TOa/Oa, an upward trend in TOa/PBa and Oa/PBa ratios was observed in older participants (>33 years), suggesting subtle age-related structural changes. Vitamin D3 levels showed no significant impact on morphometric ratios, though a slight elevation in TOa/PBa was noted in Vitamin D3-deficient participants. High-quality embryos (Class A) exhibited lower embryo area to average cleavage blastomere area (Ea/Ba) (p-value = 0.04) and TEa/Ba ratios (p-value = 0.0509), reflecting uniform cleavage and superior blastomere organization. In contrast, lower-quality zygotes (Class C) and oocytes showed irregularities in pronuclear and polar body dimensions, correlating with reduced developmental potential. These findings suggest that morphometric parameters could serve as valuable indicators of gamete and embryo quality. When used in conjunction with other assessment methods, these metrics may enhance embryo selection precision, potentially contributing to improved implantation success and advancements in reproductive medicine.